Are there lingering effects of egg thiamine deficiency (M74) in thiamine-treated Baltic Sea salmon (Salmo salar) juveniles? - Dahlgren, Elin; Persson, Lo; Näslund, Joacim (ELSEVIER, 2025)
Temporal fluctuation of thiamine deficiency is a well-documented phenomenon in Atlantic salmon ( Salmo salar) from the Baltic Sea. The deficiency causes increased levels of fry mortality (M74-syndrome). Although the cause for the deficiency in salmon remains somewhat unclear, the mortality rate can be significantly reduced by bathing alevins in thiamine solution. However, it is not known whether thiamine supplementation at the alevin stage successfully treats all other potential adverse effects associated to thiamine deficiency during the embryonic stages of development. To investigate how thiamine deficiency affects growth and survival in thiamine treated and untreated salmon during the first summer, fertilized eggs with known thiamine content were sorted into four groups: Very low, , Low, , Medium and High thiamine content (all having thiamine levels above critical levels where mortality is inevitable if left untreated). Half of each group was treated with thiamine according to standardized hatchery procedures and half was left untreated as control. Mortality was monitored continuously, and body length and-mass were recorded after the initial growing season (five months after hatching). The results showed that fish with very low initial levels of thiamine grew smaller even if treated with supplemental thiamine. This indicates a potential disturbance of individuals suffering from early thiamine deficiency.